2020
DOI: 10.1007/s00429-020-02111-9
|View full text |Cite
|
Sign up to set email alerts
|

MRI spectroscopic and tractography studies indicate consequences of long-term ketogenic diet

Abstract: To maintain its functional abilities, the mature brain obtains energy from glucose produced in carbohydrate metabolism. When carbohydrates are eliminated from the diet, the energy comes from the oxidation of fatty acids. In this metabolic state called ketosis, ketone bodies are formed: β-hydroxybutyric acid (bHb), acetone, and acetoacetate as alternative source of energy passing through the blood-brain barrier easily. The ketosis state can be achieved through various strategies like caloric restriction, supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…It may suggest a generalized nature of the previously described changes. In contrast, our studies on normal animals, that were fed KD for 4 months, showed increases in the number of myelinated bers passing through the hippocampal formation, striatum, internal capsule and pons (Gzieło et al, 2020). These differences might depend on the length of time during which the diet was applied.…”
Section: Discussioncontrasting
confidence: 82%
“…It may suggest a generalized nature of the previously described changes. In contrast, our studies on normal animals, that were fed KD for 4 months, showed increases in the number of myelinated bers passing through the hippocampal formation, striatum, internal capsule and pons (Gzieło et al, 2020). These differences might depend on the length of time during which the diet was applied.…”
Section: Discussioncontrasting
confidence: 82%
“…This may indicate that metabolic ketosis furnishes mitochondria with TCA cycle substrates ( 17 ). Furthermore, a 4-month KD elevated Glu and glutamine in young adult rats ( 36 ), and although human patients with epilepsy did not show differences in posterior cingulate cortical Glu measures compared to controls, elevated Glu concentrations predicted short-term freedom from seizures, hence indicating clinical relevance of elevated Glu in epilepsy ( 37 ). In the meantime, a recent study found that acetone and BHB acted as inhibitors of Glu at the excitatory NMDA ( N -methyl- d -aspartate) receptors ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our preclinical finding that a history of KD decreased alcohol consumption, however, merits further investigation for we do not have clinical data on long-lasting effects of KD on alcohol abstinence. Although preclinical studies have not been reported on long-lasting effects of KD on brain glucose metabolism, there are reports of long-lasting changes in brain structure and neurochemistry following a KD, including elevated glutamate and glutamine ( 36 ). Thus, future studies are needed to assess whether there are long-lasting changes in brain glucose metabolism that persist after KD discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in a mouse model of Alzheimer's Disease (triple transgenic Alzheimer's 3xTgAD, which shows reduced brain glucose utilization) showed higher hippocampal glutamate and α-ketoglutarate (a precursor of glutamate) in animals who received a KE diet compared to regular chow and a positive correlation between glutamate and α-ketoglutarate levels in both groups ( 50 ). Thus, nutritional ketosis appears to furnish mitochondria with TCA cycle substrates ( 38 ), as evidenced by the finding that a 4-month KD elevated glutamate and glutamine in young adult rats ( 81 ). Although patients with epilepsy did not show differences from controls in posterior cingulate cortical glutamate measures, patients' elevated glutamate concentrations predicted short-term freedom from seizures, supporting the clinical relevance of glutamate concentrations in epilepsy ( 82 ).…”
Section: Potential Mechanisms Of Action For the Therapeutic Effects Of Ketosis In Alcohol Use Disordermentioning
confidence: 99%